Isokinetic performance of shoulder external and internal rotators in adolescent female handball athletes - Bonetti, L. V.; Zardo, F.; Candiago, B. G.; Finger, A. L. Temp; De Marchi, T.; Tadiello, G. S. (Science & Sports, 2019)
Objectives: The aim of this study was to analyse the difference between the dominant and non-dominant shoulder's external and internal rotators in adolescent female handball players. Methods: The information provided by database concerning the isokinetic evaluation of shoulder muscles from 21 female handball athletes between the ages of 14-17 years old were analyzed. The isokinetic dynamometer was used in a concentric-concentric mode for the shoulder external and internal rotators muscles at angular velocities of 60°/s and 180°/s. Results: Isokinetic peak torque for external and internal rotators was not different between upper limbs. For external/internal rotators ratio, no difference was shown between the dominant and non-dominant limbs for the both angular velocities studied. Conclusion: This study demonstrated that despite repetitive overhead throwing performed by the dominant upper limb, it was not the cause of limbs isokinetic imbalances for adolescent female handball players.